Glycerol: Production, consumption, prices, characterization and new trends in combustion - Quispe, César A.G. [UNESP]; Coronado, Christian J.R.; Carvalho Jr., João A. [UNESP] (Elsevier, 2013)
The demand for petroleum has been rising rapidly due to increasing industrialization and modernization. This economic development has led to a huge demand for energy, most of which is derived from fossil fuel. However, the limited reserve of fossil fuel has led many researchers to look for alternative fuels which can be produced from renewable feedstock. Increasing fossil fuel prices have prompted the global oil industry to look at biodiesel, which is from renewable energy sources. Biodiesel is produced from animal fats and vegetable oils and has become more attractive because it is more environmentally friendly and is obtained from renewable sources. Glycerol is the main by-product of biodiesel production; about 10% of the weight of biodiesel is generated in glycerol. The large amount of glycerol generated may become an environmental problem, since it cannot be disposed of in the environment. In this paper, an attempt has been made to review the different approaches and techniques used to produce glycerol (hydrolysis, transesterification, refining crude glycerol). The world biodiesel/glycerol production and consumption market, the current world glycerin and glycerol prices as well as the news trends for the use of glycerol mainly in Brazil market are analyzed. The technological production and physicochemical properties of glycerol are described, as is the characterization of crude glycerol obtained from different seed oil feedstock. Finally, a simple way to use glycerol in large amounts is combustion, which is an advantageous method as it does not require any purification. However, the combustion process of crude glycerol is not easy and there are technological difficulties. The news and mainly research about the combustion of glycerol was also addressed in this review. © 2013 Elsevier Ltd.
Keywords: Biodiesel; Byproducts; Combustion; Glycerol; Biodiesel production; Economic development; Environmental problems; Environmentally-friendly; Physicochemical property; Production and consumption; Renewable energy source; Renewable feedstocks; Alternative fuels; Commerce; Costs; Feedstocks; Fossil fuels; Oils and fats; Proven reserves; Renewable energy resources